Information and communication technology (ICT) as a metacognitive strategy for reconstructing science concepts - Locatelli, Solange Wagner (LUMAT-B: International Journal on Math, Science and Technology Education, 2018)
It is essential to consider different strategies to help students rebuild chemical concepts in the classroom. This research was done with undergraduates from a public university in São Paulo (Brazil), in which google forms - an ICT tool - was used to mediate the interaction between students and teacher. The objective of the class was to externalize the students' previous knowledge about the subject of heat and energy that would be the basis for the continuation of studies in thermochemistry. Based on an article evidencing alternative conceptions of these concepts, three questions were elaborated in which the students had to answer before the beginning of the lesson. During the class, the teacher was projecting the results, which were automatically expressed in graphs and thus the discussions surrounding the questions were being processed, enabling the deconstruction and reconstruction of previous ideas and the correct construction of scientific concepts. The results indicate that the metacognitive strategy using ICT was efficient, since the students could externalize and reconstruct their concepts collectively - metacognitive exercise. In addition, the results were positive in terms of behavior, motivation and the acquisition of technological attitudes and skills, since many students were unaware of the tool. Therefore, using metacognitive strategies in the teaching of science is recommended, as it allows the possibility to reconstruct scientific concepts, and the use of ICT can be a facilitator to know students' previous conceptions and to bring them to light for collective discussion.